High-pressure synthesis, spin-glass behaviour, and magnetocaloric effects in FexTi2S4 heideite sulphides. Issue 42 (11th October 2022) - Silva Jr, R. S.; Gainza, J.; Rodrigues, J. E.; Martínez, L.; Céspedes, E.; Nemes, N. M.; Martínez, J. L.; Alonso, J. A.
Abstract : A rapid high-pressure preparation method (3.5 GPa) yields Fe x Ti2 S4 Heideite-type phase. Magnetism offers a complex scenario with AFM to FM-like interactions. The magnetocaloric effect yields significant entropy and relative cooling power. Abstract : Intercalation compounds based on layered TiS2 sulphides are gaining much attention, since the incorporation of transition metals often dramatically change the physical properties and unlocks new intriguing phenomena. Here, we report a rapid high-pressure preparation method under 3.5 GPa at moderate temperatures for the synthesis of Fe x Ti2 S4 polycrystalline materials, starting from TiS2 and Fe metals. Three different compositions with x = 0.24, 0.32, and 0.42 have been stabilized at decreasing temperatures in the range of 800–900 °C; at room temperature, the crystallographic features have been probed by a neutron powder diffraction (NPD) experiment for the x = 0.42 sample. All the compounds crystallize in a Heideite-type phase with space group C 12/ m 1; the structure consists of layers of [TiS6 ] octahedra sharing edges with Fe atoms located in between the layers, also in octahedral coordination. The NPD study unveils a discrete Fe/Ti inversion (<6%) at the TiS2 layers. The surface chemistry from XPS at Fe 2p and Ti 2p core levels revealed the presence of Fe 2+ in all samples, whereas the Ti main contribution mainly arises from the Ti 3+ state, with a smaller contribution of Ti 2+ and Ti 4+ states. The magnetic properties stemming from Fe 2+ and Ti 3+ spins offer a complex scenario with antiferromagnetic interactions, characterized by a strongly negative Weiss constant ( e.g. θ W = −398 K for x = 0.42), predominant for the Fe-rich phase Fe0.42 Ti2 S4, combined with ferromagnetic-like interactions as x decreases ( e.g. θ W = 204 K for x = 0.24), leading to spin–glass or cluster–glass behaviours. The study of the magnetocaloric effect yields relative cooling power (RCP) values at a 7 T of 135.3, 124.5, and 96.0 J kg −1 for the x = 0.24, 0.32 and 0.42 samples, respectively, better than other transition-metal sulphides already reported in the literature, with a temperature stability that is desirable for an ideal Ericson refrigeration cycle.